Pegcetacoplan versus Eculizumab in Paroxysmal Nocturnal Hemoglobinuria - Hillmen, Peter; Szer, Jeff; Weitz, Ilene; Röth, Alexander; Höchsmann, Britta; Panse, Jens; Usuki, Kensuke; Griffin, Morag; Kiladjian, Jean-Jacques; de Castro, Carlos; Nishimori, Hisakazu; Tan, Lisa; et al. (The New England journal of medicine, 2021)
Anemia associated with PNH is caused by hemolysis. The C5 inhibitor eculizumab blocks intravascular hemolysis, but anemia often persists owing to extravascular hemolysis. Pegcetacoplan, an inhibitor of C3, prevents extravascular hemolysis. After 16 weeks of treatment, hemoglobin increased nearly 4 g per deciliter in 41 patients treated with pegcetacoplan, and 85% no longer needed transfusion.